A Cluster Randomized Controlled Trial of the MyFamilyPlan Online Preconception Health Education Tool. Issue 4 (May 2018) - Batra, Priya; Mangione, Carol M.; Cheng, Eric; Steers, W. Neil; Nguyen, Tina A.; Bell, Douglas; Kuo, Alice A.; Gregory, Kimberly D.
Purpose: To evaluate whether exposure to MyFamilyPlan—a web-based preconception health education module—changes the proportion of women discussing reproductive health with providers at well-woman visits. Design: Cluster randomized controlled trial. One hundred thirty participants per arm distributed among 34 clusters (physicians) required to detect a 20% change in the primary outcome. Setting: Urban academic medical center (California). Participants: Eligible women were 18 to 45 years old, were English speaking, were nonpregnant, were able to access the Internet, and had an upcoming well-woman visit. E-mail and phone recruitment between September 2015 and May 2016; 292 enrollees randomized. Intervention: Intervention participants completed the MyFamilyPlan module online 7 to 10 days before a scheduled well-woman visit; control participants reviewed standard online preconception health education materials. Measures: The primary outcome was self-reported discussion of reproductive health with the physician at the well-woman visit. Self-reported secondary outcomes were folic acid use, contraceptive method initiation/change, and self-efficacy score. Analysis: Multilevel multivariate logistic regression. Results: After adjusting for covariates and cluster, exposure to MyFamilyPlan was the only variable significantly associated with an increase in the proportion of women discussing reproductive health with providers (odds ratio: 1.97, 95% confidence interval: 1.22-3.19). Prespecified secondary outcomes were unaffected. Conclusion: MyFamilyPlan exposure was associated with a significant increase in the proportion of women who reported discussing reproductive health with providers and may promote preconception health awareness; more work is needed to affect associated behaviors.